2020
DOI: 10.1007/s12325-020-01571-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Novel Biomarkers Ready for Evaluation in Low-Prevalence Populations for the Early Detection of Upper Gastrointestinal Cancers: A Systematic Review

Abstract: Introduction Detecting upper gastrointestinal (GI) cancers in primary care is challenging, as cancer symptoms are common, often non-specific, and most patients presenting with these symptoms will not have cancer. Substantial investment has been made to develop biomarkers for cancer detection, but few have reached routine clinical practice. We aimed to identify novel biomarkers for upper GI cancers which have been sufficiently validated to be ready for evaluation in low-prevalence populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…These have been reported elsewhere [12]. The protocol for this review was registered on PROSPERO (registration ID CRD42020165005) and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis of Diagnostic Test Accuracy Studies (PRISMA-DTA) statement was followed [13].…”
Section: Search Strategy and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…These have been reported elsewhere [12]. The protocol for this review was registered on PROSPERO (registration ID CRD42020165005) and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis of Diagnostic Test Accuracy Studies (PRISMA-DTA) statement was followed [13].…”
Section: Search Strategy and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Most studies involve a small number of samples with no validation group (123)(124)(125). The investigations involving small cohorts are associated with a high risk of false-positive cases, which has hindered or delayed the clinical application of diagnostic and prognostic biomarkers (126). To overcome these limitations, Azizian et al (127) performed microarray analysis of a training set comprising 45 preoperative biopsies from patients with rectal cancer to identify potential miRNAs that can predict tumor regression grade and other clinical parameters.…”
Section: Ncrnas As Predictive Biomarkers For Rt Response In Patients ...mentioning
confidence: 99%
“…This study highlights the need for more biomarker studies that consider the primary care/community setting as their intended population. It suggested that apoA2-ATQ/AT and pepsinogens (PGI and PGII) were the most promising biomarkers for pancreatic cancer and gastric cancer, respectively [ 23 ].…”
Section: Future Perspectivementioning
confidence: 99%